EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA. (1st December 2019) - Wang, Yan‐Ping; Zhang, Lin‐Sen; Mu, Yan; Liu, Wei‐Hong; Guo, Fu‐Xing; Chang, Tian‐Ran
Abstract: Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd. Résumé: Sur le plateau chinois de Loess, les ressources en eau sont rares et l'efficacité de l'irrigation est un problème épineux. Les méthodes traditionnelles d'irrigation goutte à goutte au sol (SDI) n'ont pas permis d'améliorer l'efficacité de l'irrigation et de réduire l'évaporation de surface dans la région. Une méthode d'irrigation par injection de zone racinaire avec un faible risque de colmatage (RII) facile à installer et facile à utiliser, qui utilise des appareils favorisant l'infiltration souterraine (SIPA) pour acheminer l'eau directement dans la zone racinaire, a été conçue et testée dans un verger de pommiers pendant 3 ans dans le nord du Shaanxi, en Chine. Dans une couche de sol de 0 à 0.6 m (où les racines des pommiers sont concentrées), la méthode RII a produit une teneur en eau du sol toujours plus élevée que la méthode SDI pendant les trois saisons de croissance. La teneur en eau du sol était constamment supérieure à 60% de la capacité du terrain, répondant ainsi aux besoins en eau des pommiers fruitiers. En outre, la méthode RII a permis de réduire la dessiccation du sol, d'augmenter considérablement le rendement en pommes et d'améliorer la qualité des fruits par rapport à la méthode SDI utilisant le même volume d'eau d'irrigation. L'efficacité de l'irrigation et l'efficacité de l'utilisation de l'eau ont été améliorées avec la méthode RII. Ces résultats fournissent une base théorique pour l'utilisation de la méthode d'irrigation RII dans les vergers de pommiers dans les régions semi‐arides, ce qui pourrait améliorer la conservation de l'eau et la durabilité de la production de pommes. © 2019 John Wiley & Sons, Ltd.